Regulatory mechanism and research progress of ferroptosis in obstetrical and gynecological diseases - Wang, Xinyue; Wei, Yanchen; Wei, Fangyi; Kuang, Haibin (Frontiers in Cell and Developmental Biology, 2023)
Ferroptosis is a novel type of regulated cell death driven by iron-dependent lipid peroxidation, which is distinguished from traditional types of programmed cell death, such as apoptosis, proptosis and necrosis et al. Impaired iron homeostasis, lipid peroxidation and antioxidants depletion are three hallmarks of ferroptosis. Over the past years, emerging studies support the notion that ferroptosis might be involved in the pathology of obstetrical and gynecological diseases, including preeclampsia (PE), endometriosis (EMs) and polycystic ovarian syndrome (PCOS). In the PE condition, the high sensitivity of trophoblasts towards ferroptosis has been found to potentially link to inflammation, suboptimal vascular remodeling and aberrant hemodynamics, which are three prominent pathophysiological features of PE. As for EMs, compromised ferroptosis of endometrial cells was associated with the formation ectopic lesions, whereas in the nearby lesions, the presence of ferroptosis was suggested to promote the progression of EMs, contributing to the relative clinical manifestations. Ferroptosis has been implicated a crucial role in the initiation of ovarian follicular atresia, which might help to manage ovulation in PCOS patients. Taken together, this review explored the basis of ferroptosis mechanisms and comprehensively summarized the latest discovery of roles of ferroptosis on PE, EMs and PCOS, gaining a deeper insight into the pathogenesis of these obstetrical and gynecological diseases and investigation of novel therapeutic interventions.